Black skin, white masks - Fanon, Frantz (New York Grove Press, 2008)
Few modern voices have had as profound an impact on the black identity and critical race theory as Frantz Fanon, and Black Skin, White Masks represents some of his most important work. Fanon$1 (Bs masterwork is now available in a new translation that updates its language for a new generation of readers.s